(3dDdD GdHMQjf aj GdELGRI dbQJj GdYjfjfs - (3jhSa Hf CMeO Hf EHQGgje GdOQGRj GdHMQGfj, GHf oYrUoahQ,J (B1186 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYdfG ef Cgd GdQhGjI hfhQ bdhHfG HCfhGQ GdeYQaI hGdOQGjI s
(3BNQgG (B:s
(3hBNQ g eHJhQ , hNQ GdehLhO efg (B: (3GHf SjGQI , CHhYHOGddg GdcGJH, cGf ef cJGH Bd WGgQ s
(3Vef eLehY s
(3hgj ELGRI ef jhSa Hf CMeO Hf UGdM Hf YUahQ GdOQGRj GdHMQGfj GdeJhaj SfI (B1186(3g`s
(3dJdejPjf ef JdGejPg geG Nda Hf YHO Ydj hMSjf GHf eMeOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B268s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B405 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B353 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs